Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1063/1.372094
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metalorganic decomposition-derived SrBi2Ta2O9 thin films with different thicknesses

Abstract: Properties of SrBi 2 Ta 2 O 9 ferroelectric thin films prepared by a modified metalorganic solution deposition technique Appl.Ferroelectric capacitors having sputtered Pt bottom and top electrodes and metalorganic decomposition derived ferroelectric thin films of SrBi 2 Ta 2 O 9 ͑SBT͒ were prepared. The thickness effects on the structure, surface morphology, and electrical properties of SBT thin films were studied and discussed. Structure and surface morphology were analyzed by x-ray diffraction and atomic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…In particular, the film of 240 nm thickness exhibits a considerable higher 2Pr of ∼24 μC/cm 2 and a coercive field of 151 kV/cm, as comparable to the randomly orientated BNdT film prepared by other methods [8,9]. A similar polarization loop is shown for the film of 160 nm thickness, although there is a slight increase in coercive filed, which is related to the blocking layer that has been commonly observed in ferroelectric films [11,13]. In comparison, there is an obvious change in polarization loop for the BNdT of 120 nm in thickness, where a much slimmer P-E hystereis loop is observed.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…In particular, the film of 240 nm thickness exhibits a considerable higher 2Pr of ∼24 μC/cm 2 and a coercive field of 151 kV/cm, as comparable to the randomly orientated BNdT film prepared by other methods [8,9]. A similar polarization loop is shown for the film of 160 nm thickness, although there is a slight increase in coercive filed, which is related to the blocking layer that has been commonly observed in ferroelectric films [11,13]. In comparison, there is an obvious change in polarization loop for the BNdT of 120 nm in thickness, where a much slimmer P-E hystereis loop is observed.…”
Section: Resultssupporting
confidence: 56%
“…To understand the ferroelectric thin films towards the nanometer scale, there has been attempt to refine the film thickness, which indeed has led to several unique phenomena in their ferroelectric behaviors [11][12][13]. Realization of improved electrical properties at reduced film thickness is of considerable interest, as the thin film and device technologies are driving towards miniaturization, for example for small cell size and low operating polarization voltage of FRAM (at 3 V or 5 V) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been employed for the synthesis of thin films of SBN and, in a larger extent, its parent compound SrBi 2 Ta 2 O 9 (SBT), such as sol-gel [65][66][67], Metal-Organic Solution Deposition [68][69][70], metal-organic chemical vapor deposition (MOCVD) [71], polymeric precursors (Pechini process) [72], r.f. sputtering [73][74][75] and pulsed laser deposition (PLD) [61][62][63][76][77][78][79][80][81][82][83], including plasma-assisted PLD [84].…”
Section: Ferroelectric Thin Films 31 Growth Methodsmentioning
confidence: 99%
“…Accordingly, the grain size is able to be large without a surface-roughening problem. It is reported that large grain size is favorable for enhancing electrical properties [21]. These microstructure characteristics such as a smooth surface morphology and a large grain size are superior properties to those of the elliptical grain growth.…”
Section: Article In Pressmentioning
confidence: 98%